Clinical similarity of biosimilar ABP 501 to adalimumab in the treatment of patients with moderate to severe plaque psoriasis: A randomized, double-blind, multicenter, phase III study - Papp, Kim; Bachelez, Herve; Costanzo, Antonio; Foley, Peter; Gooderham, Melinda; Kaur, Primal; Narbutt, Joanna; Philipp, Sandra; Spelman, Lynda; Weglowska, Jolanta; Zhang, Nan; Strober, Bruce (Journal of the American Academy of Dermatology, 2017)
ABP 501 is a biosimilar of adalimumab. We sought to compare the efficacy and safety of ABP 501 with adalimumab. This 52-week, double-blind study randomized patients with moderate to severe psoriasis to ABP 501 or adalimumab. At week 16, those with 50% or more improvement in Psoriasis Area and Severity Index score from baseline on ABP 501 continued the same treatment, whereas adalimumab-treated patients were rerandomized to adalimumab or ABP 501. Clinical similarity in Psoriasis Area and Severity Index percent improvement from baseline to week 16 (primary end point) was established if the point estimate of treatment difference and its 2-sided 95% confidence interval between groups was within equivalence margin of ±15. Patients, including those undergoing a single transition at week 16, were evaluated for safety and immunogenicity. Psoriasis Area and Severity Index percent improvement at week 16 was 80.9 for ABP 501 and 83.1 for adalimumab (least-square mean difference −2.18 [95% confidence interval −7.39 to 3.02]). Adverse events (67.2% [117/174] vs 63.6% [110/173]) and antidrug antibody incidence (55.2% [96/174] vs 63.6% [110/173]) for ABP 501 vs adalimumab were similar. Safety, including immunogenicity, was similar among groups after single transition (week 20). The 52-week data are not reported here. ABP 501 was shown to be clinically similar to adalimumab. Safety and immunogenicity were not impacted immediately after single transition (adalimumab to ABP 501).